PROTECTIVE EFFECTS OF VITAMIN C ON ACETAMINOPHEN-INDUCED LIVER AND KIDNEY TOXICITY IN MALE RATS - Ebhohon, Shirley Onagbonfeoana; Asoya, Ekene Victor; Iyare, Harrison Ekhorseye (FUDMA JOURNAL OF SCIENCES, 2024)
Acetaminophen (paracetamol) is a widely used over-the-counter analgesic and antipyretic medication known for its efficacy and safety when administered within recommended doses. However, overdose or prolonged use of acetaminophen can lead to severe hepatotoxicity and nephrotoxicity, posing a significant public health concern. This study aims to investigate the protective effects of vitamin C on acetaminophen-induced hepatotoxicity and nephrotoxicity in male Wistar rats. Six rats were randomly assigned to seven groups, with Group 1 designated as the control. Groups 2, 4, and 6 were given daily single oral doses of 100, 200, and 400 mg/kg of acetaminophen, respectively. Meanwhile, Groups 3, 5, and 7 received daily single oral doses of 100, 200, and 400 mg/kg of acetaminophen, followed by intraperitoneal administration of 100 mg/kg of vitamin C daily, for 14 days. Liver function markers (AST, ALT, total bilirubin, and total protein) and renal function indicators (urea and creatinine levels) were assessed, alongside antioxidant status in liver and kidney tissues through antioxidant assays (SOD, CAT, GSH, and MDA). The results demonstrated the protective influence of vitamin C on liver and kidney tissues, as indicated by the modulation of biochemical markers. These findings suggest that vitamin C may play a pivotal role in alleviating acetaminophen-induced liver and kidney damage across different dosage regimens, potentially serving as a therapeutic intervention for preventing or treating drug-induced organ injuries. Further investigations are essential to elucidate the underlying mechanisms and validate the translational potential of vitamin C as a protective agent against acetaminophen toxicity.